2017
DOI: 10.4172/2155-6105.1000312
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Predictive Algorithm that Detects Aberrant Use of Opioids in an Addiction Treatment Centre

Abstract: Introduction: Physicians prescribing opioids are at the front lines of the opioid abuse epidemic, battling to tip the scale between rising abuse rates and adequate pain control. This study evaluates the performance of an algorithm that incorporates genetic and non-genetic risk factors in accurately predicting patients at risk of Opioid Use Disorder (OUD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…A previous discovery study demonstrated that the POR predicts risk of OUD with greater specificity than either the ORT or the SOAPP ® 25. This study confirms the utility of the POR, with an entirely new cohort of patients.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A previous discovery study demonstrated that the POR predicts risk of OUD with greater specificity than either the ORT or the SOAPP ® 25. This study confirms the utility of the POR, with an entirely new cohort of patients.…”
Section: Discussionsupporting
confidence: 78%
“…The POR algorithm is a patent-protected, validated measure of opioid risk 25. In short, it combines phenotypic and genotype information to calculate a risk score that correlates with high-, moderate-, or low-risk stratification of opioid dependence,25 such that a score of 1–11 is associated with low-risk, 12–23 with moderate-risk, and ≥24 with high-risk of OUD.…”
Section: Methodsmentioning
confidence: 99%
“…Some of these gene panels and interpretative algorithms are available in the market from commercial vendors (48). While genetic approaches may be represented in the commercial marketplace as a panacea, we believe physicians should also be informed about the inherent predictive limitations in models from vendors of multi-gene panels.…”
Section: Further Research and Multi-gene Panelsmentioning
confidence: 99%
“… 11 , 12 These screening assessments, however, are based completely on subjective information. Furthermore, three previous studies demonstrated that the algorithm described herein, referred to as “profile”, performed with greater sensitivity and specificity than either the ORT or the SOAPP-R. 13 15 …”
Section: Introductionmentioning
confidence: 82%
“…The improved sensitivity and specificity of the profile over other current screening measures stems from its unique algorithm that combines clinical risk factors with objective genotypic information. 13 15 The clinical validity of the profile has been examined in multiple clinical settings, including primary care, 14 addiction treatment centers, 15 pain clinics, 13 and orthopedic clinics, 13 among others. In these studies, the high accuracy of the profile, ranging from 76% to 97%, demonstrated its diagnostic potential as a predictor of risk to opioid abuse.…”
Section: Introductionmentioning
confidence: 99%